Distinctive properties of metastasis-initiating cells - Celià-Terrassa, Toni; Kang, Yibin (Genes & development, 2016)
Primary tumors are known to constantly shed a large number of cancer cells into systemic dissemination, yet only a tiny fraction of these cells is capable of forming overt metastases. The tremendous rate of attrition during the process of metastasis implicates the existence of a rare and unique population of metastasis-initiating cells (MICs). MICs possess advantageous traits that may originate in the primary tumor but continue to evolve during dissemination and colonization, including cellular plasticity, metabolic reprogramming, the ability to enter and exit dormancy, resistance to apoptosis, immune evasion, and co-option of other tumor and stromal cells. Better understanding of the molecular and cellular hallmarks of MICs will facilitate the development and deployment of novel therapeutic strategies.